An inorganic perovskite solar cell based on phenylethyl phosphate stress regulation and a preparation method thereof
Patent Information
- Application Number
- CN202610953327.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
通过将配体分子苯乙基磷酸引入无机钙钛矿太阳电池的制备过程中,解决了现有技术中机钙钛矿太阳电池非辐射复合损失的技术问题
[0032]本发明通过将苯乙基磷酸引入钙钛矿前驱体溶液中来调节薄膜应力,并制备无机钙钛矿太阳电池。本发明发现,苯乙基磷酸兼具化学缺陷钝化与物理应力缓冲双重功能。首先,其分子结构中的磷酸基团具备强配位能力,能够与钙钛矿晶界或表面处存在的欠配位铅离子形成稳定的配位键,从而有效钝化铅缺陷,显著降低薄膜内部的缺陷态密度,并缓解因缺陷引发的局部应力集中。其次,苯乙基磷酸中的柔性烷基链可通过分子构象的微调,缓解由于晶格失配或热应力积累所产生的残余应力,进而抑制应力诱导的晶格畸变与离子迁移,共同提升无机钙钛矿薄膜的质量,最终实现高效稳定的无机钙钛矿太阳电池。
Smart Images

Figure CN123021883A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy, specifically relating to an inorganic perovskite solar cell based on stress regulation using phenylethyl phosphoric acid and its preparation method. Background Technology
[0002] Inorganic perovskite solar cells have attracted much attention due to their excellent thermal stability. However, to achieve good crystallinity and photoelectric properties, inorganic perovskites typically require annealing temperatures higher than those of organic-inorganic hybrid perovskites. Higher annealing temperatures create significant temperature gradients within the material, and residual stress is directly and positively correlated with these temperature gradients; the larger the temperature gradient, the more significant the residual stress generated within the material. Simultaneously, inorganic perovskites possess an inherent structural characteristic of ion size mismatch, which induces inherent strain in the internal lattice, causing them to often experience significant residual tensile strain after annealing. This structural heterogeneity caused by strain effects not only disrupts the integrity of the perovskite lattice but also introduces intrinsic instabilities.
[0003] The presence of residual strain has several negative impacts on device performance. First, strain affects the band structure of perovskite materials, causing a shift in the energy level arrangement at the interface, thus hindering the effective separation and transport of photogenerated carriers. Second, residual strain is closely related to the defect density within the material; the formation of halogen vacancies increases under compressive strain but decreases under tensile strain. This means that tensile strain lowers the energy barrier to defect formation, leading to an increase in defect density, which in turn exacerbates nonradiative recombination losses, ultimately limiting the photoelectric conversion efficiency of the device.
[0004] In summary, residual strain caused by thermal expansion coefficient mismatch and inherent lattice distortion is a key factor affecting the efficiency and stability of inorganic perovskite solar cells. How to effectively control or eliminate this residual stress and reduce the resulting non-radiative recombination losses is one of the urgent problems to be solved in inorganic perovskite solar cells. Summary of the Invention
[0005] The purpose of this invention is to overcome the aforementioned shortcomings of the prior art and provide a method for preparing inorganic perovskite solar cells based on stress regulation using phenylethyl phosphoric acid. By introducing the ligand molecule phenylethyl phosphoric acid into the preparation process of inorganic perovskite solar cells, the technical problem of non-radiative recombination loss in existing inorganic perovskite solar cells is solved.
[0006] In the annealing process of inorganic perovskite thin films, the phosphate groups in the phenylethyl phosphoric acid molecule possess strong coordination ability, enabling them to form stable coordination bonds with undercoordinated lead ions at perovskite grain boundaries or surfaces. This effectively passivates lead defects, reduces defect state density, and alleviates local stress concentration. Simultaneously, the alkyl chains in phenylethyl phosphoric acid can alleviate residual stress caused by lattice mismatch or thermal stress accumulation through fine-tuning of molecular conformation, suppressing stress-induced lattice distortion and ion migration, ultimately achieving a highly efficient and stable inorganic perovskite solar cell.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides an inorganic perovskite light-absorbing layer, which is obtained by dissolving a ligand material in a perovskite precursor solution, depositing it using a one-step spin-coating method in a nitrogen environment, and annealing it in an air environment; wherein the ligand molecule is phenylethyl phosphoric acid, and the concentration in the inorganic perovskite precursor solution is 0.5 ~ 3.0 mg / mL.
[0009] In a second aspect, the present invention provides an inorganic perovskite solar cell based on phenylethyl phosphoric acid for stress regulation. The structure of the inorganic perovskite solar cell, stacked from bottom to top, consists of: a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a buffer layer, and a metal electrode. The perovskite light-absorbing layer is the inorganic perovskite light-absorbing layer provided in the first aspect of the present invention, and its thickness is 300 ~ 900 nm.
[0010] Thirdly, the present invention provides a method for preparing inorganic perovskite solar cells based on stress regulation using phenylethyl phosphoric acid, the method comprising:
[0011] (1) Obtain a conductive substrate, spin-coat a hole transport layer solution onto the conductive substrate, and anneal to prepare a hole transport layer;
[0012] (2) An inorganic perovskite precursor solution containing the ligand molecule phenylethyl phosphoric acid was spin-coated onto the hole transport layer and then annealed to prepare a perovskite light-absorbing layer.
[0013] (3) Spin-coating the electron transport layer precursor solution onto the perovskite light-absorbing layer to prepare the electron transport layer;
[0014] (4) A buffer layer is prepared by spin-coating on the electron transport layer;
[0015] (5) Fabricate a metal electrode on the buffer layer;
[0016] The concentration of the ligand molecule phenethyl phosphoric acid in the inorganic perovskite precursor solution is 0.5 ~ 3.0 mg / mL.
[0017] Furthermore, the conductive substrate mentioned in step (1) is any one of ITO conductive glass, transparent conductive flexible plastic, crystalline silicon substrate, copper indium gallium selenide substrate, etc.
[0018] Furthermore, the hole transport layer mentioned in step (1) is SAMs or NiO. X The coating can be made of any one or more of the following materials: PTAA, P3HT, P3CT, X55, and X60; the spin coating speed is 1000-5000 rpm / min and the time is 20-40 s; the annealing conditions are: annealing in ambient air at 100-150℃ for 10-30 min.
[0019] Furthermore, the solvent for the perovskite precursor solution in step (2) is any one or a mixture of dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methylpyrrolidone, and the solute is CsPbI. X Br 3-X The concentration of the solute is 0.6 ~ 1.2 mol / L;
[0020] Furthermore, the perovskite light-absorbing layer described in step (2) is prepared by spin-coating a perovskite precursor solution followed by annealing. The spin-coating speed is 1000 ~ 3000 rpm / min and the time is 70 ~ 120 s. The annealing conditions are: annealing at 150 ~ 210℃ in ambient air for 5 ~ 10 min.
[0021] Furthermore, the electron transport layer mentioned in step (3) is a PC. 61 BM, C 60 Any one or two materials; spin coating speed of 1000 ~ 5000 rpm / min, time of 20 ~ 40 s;
[0022] Furthermore, the buffer layer mentioned in step (4) is any one of BCP, ZnO, or TPBi; the spin coating speed is 3000~6000 rpm / min, and the time is 20~40 s;
[0023] Furthermore, the metal electrode mentioned in step (5) is any one of gold, silver, or copper, deposited at 60-100 nm by vacuum evaporation.
[0024] Fourthly, this invention also provides the application of a coordination molecule in an inorganic perovskite solar cell. The coordination molecule is phenylethyl phosphoric acid. This ligand molecule is dissolved in a perovskite precursor solution, deposited using a one-step spin-coating method in a nitrogen atmosphere, and annealed in air to obtain an inorganic perovskite light-absorbing layer. Based on this coordination molecule, residual stress is released and defects are passivated, resulting in a high-quality perovskite thin film for use in the following structural devices:
[0025] a. Inorganic or organic-inorganic hybrid perovskite single-junction solar cells;
[0026] b. Inorganic or organic-inorganic hybrid perovskite / crystalline silicon tandem solar cells;
[0027] c. Inorganic or organic-inorganic hybrid perovskite / organic tandem solar cells;
[0028] d. Inorganic or organic-inorganic hybrid perovskite / copper indium gallium selenide tandem solar cells;
[0029] e. All-perovskite tandem solar cells;
[0030] f. All-inorganic perovskite tandem solar cells.
[0031] Advantages and positive effects of the present invention:
[0032] This invention modulates thin-film stress and prepares inorganic perovskite solar cells by introducing phenylethyl phosphoric acid into a perovskite precursor solution. The invention reveals that phenylethyl phosphoric acid possesses dual functions: chemical defect passivation and physical stress buffering. First, the phosphate groups in its molecular structure have strong coordination capabilities, forming stable coordination bonds with undercoordinated lead ions present at perovskite grain boundaries or surfaces. This effectively passivates lead defects, significantly reduces the defect state density within the thin film, and alleviates localized stress concentration caused by defects. Second, the flexible alkyl chains in phenylethyl phosphoric acid can alleviate residual stress caused by lattice mismatch or thermal stress accumulation through fine-tuning of molecular conformation. This, in turn, suppresses stress-induced lattice distortion and ion migration, jointly improving the quality of the inorganic perovskite thin film and ultimately achieving a highly efficient and stable inorganic perovskite solar cell. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the structure of an inorganic perovskite solar cell according to a specific embodiment of the present invention;
[0034] Figure 2 This is a current-voltage characteristic curve of an inorganic perovskite solar cell prepared based on a 1.0 mol / L solution containing 0.5 mg / mL phenylethyl phosphate inorganic perovskite precursor, according to a specific embodiment of the present invention.
[0035] Figure 3 This is a current-voltage characteristic curve of an inorganic perovskite solar cell prepared based on a 1.0 mol / L solution containing 1.0 mg / mL phenylethyl phosphate inorganic perovskite precursor, according to a specific embodiment of the present invention.
[0036] Figure 4This is a current-voltage characteristic curve of an inorganic perovskite solar cell prepared based on a 1.0 mol / L solution containing 1.5 mg / mL phenylethyl phosphate inorganic perovskite precursor, according to a specific embodiment of the present invention.
[0037] Figure 5 This is a current-voltage characteristic curve of an inorganic perovskite solar cell prepared based on a 1.0 mol / L solution containing 3.0 mg / mL phenylethyl phosphate inorganic perovskite precursor, according to a specific embodiment of the present invention.
[0038] Figure 6 This is a current-voltage characteristic curve of an inorganic perovskite solar cell prepared based on a 0.8 mol / L solution containing 1.5 mg / mL phenylethyl phosphate inorganic perovskite precursor, according to a specific embodiment of the present invention.
[0039] Figure 7 This is a current-voltage characteristic curve of an inorganic perovskite solar cell prepared based on a 1.0 mol / L inorganic perovskite precursor solution without phenylethyl phosphate, according to a specific embodiment of the present invention. Detailed Implementation
[0040] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] This invention provides an inorganic perovskite light-absorbing layer incorporating the ligand molecule phenylethyl phosphoric acid, and its application in inorganic perovskite solar cells. The method for fabricating inorganic perovskite solar cells based on stress regulation using phenylethyl phosphoric acid provided by this invention modifies and optimizes the inorganic perovskite thin film using phenylethyl phosphoric acid as a ligand molecule, thereby reducing defect state density and alleviating residual stress, achieving a highly efficient and stable inorganic perovskite solar cell. See [link to relevant documentation]. Figure 1 The battery structure is stacked from bottom to top as a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a buffer layer, and a metal electrode.
[0042] Example 1:
[0043] This invention provides a method for fabricating inorganic perovskite solar cells based on stress-regulated phenylethyl phosphoric acid, comprising the following steps:
[0044] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned with detergent, deionized water and isopropanol for 30 min in sequence, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean ITO conductive glass substrate with good wettability.
[0045] 2. Add 20 mg NiO XNiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0046] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0047] 4. Dissolve CsI, HPbI3, and PbBr2 in a mixed solution of dimethylformamide and dimethyl sulfoxide in a 1:1 volume ratio (molar ratio), and add 0.5 mg / mL phenylethyl phosphoric acid. Heat and stir at 60°C under nitrogen atmosphere until completely dissolved to obtain a 1.0 mol / L CsPbI solution containing 0.5 mg / mL phenylethyl phosphoric acid. X Br 3-X Perovskite precursor solution;
[0048] 5. Spin-coat the perovskite solution obtained in step 4 onto the hole transport layer obtained in step 3 at a rotation speed of 2500 rpm / min for 90 s; then anneal at 180℃ for 5 min in ambient air; thus preparing an inorganic perovskite light-absorbing layer with a concentration of 1.0 mol / L containing 0.5 mg / mL phenylethyl phosphoric acid.
[0049] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain an electron transport layer solution;
[0050] 7. The electron transport layer solution obtained in step 6 was spin-coated onto the inorganic perovskite light-absorbing layer obtained in step 5 using a one-step spin-coating method. The spin-coating speed was 2000 rpm / min and the spin-coating time was 30 s to prepare the electron transport layer.
[0051] 8. Dissolve 0.5 mg BCP in 1 mL of isopropanol and stir until completely dissolved to obtain a buffer solution;
[0052] 9. Spin-coat the buffer layer solution obtained in step 8 onto the electron transport layer obtained in step 7 at a rotation speed of 5000 rpm / min and a spin-coating time of 30 s to prepare the buffer layer;
[0053] 10. An 80 nm thick silver film is deposited on the buffer layer obtained in step 9 to obtain an inorganic perovskite solar cell.
[0054] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 2 As shown, at AM1.5, 100 mW / cm 2Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.215 V and a short-circuit current density of 20.28 mA / cm². 2 The fill factor is 82.41%, and the efficiency is 20.31%.
[0055] Example 2:
[0056] This invention provides a method for fabricating inorganic perovskite solar cells based on stress-regulated phenylethyl phosphoric acid, comprising the following steps:
[0057] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned with detergent, deionized water and isopropanol for 30 min in sequence, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean ITO conductive glass substrate with good wettability.
[0058] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0059] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0060] 4. Dissolve CsI, HPbI3, and PbBr2 in a mixed solution of dimethylformamide and dimethyl sulfoxide in a 1:1 volume ratio (molar ratio), and add 1.0 mg / mL phenylethyl phosphoric acid. Heat and stir at 60°C under nitrogen atmosphere until completely dissolved to obtain a 1.0 mol / L CsPbI solution containing 1.0 mg / mL phenylethyl phosphoric acid. X Br 3-X Perovskite precursor solution;
[0061] 5. Spin-coat the perovskite solution obtained in step 4 onto the hole transport layer obtained in step 3 at a rotation speed of 2500 rpm / min for 90 s; then anneal at 180℃ for 5 min in ambient air; thus preparing an inorganic perovskite light-absorbing layer with a concentration of 1.0 mol / L containing 1.0 mg / mL phenylethyl phosphoric acid.
[0062] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain an electron transport layer solution;
[0063] 7. The electron transport layer solution obtained in step 6 was spin-coated onto the inorganic perovskite light-absorbing layer obtained in step 5 using a one-step spin-coating method. The spin-coating speed was 2000 rpm / min and the spin-coating time was 30 s to prepare the electron transport layer.
[0064] 8. Dissolve 0.5 mg BCP in 1 mL of isopropanol and stir until completely dissolved to obtain a buffer solution;
[0065] 9. Spin-coat the buffer layer solution obtained in step 8 onto the electron transport layer obtained in step 7 at a rotation speed of 5000 rpm / min and a spin-coating time of 30 s to prepare the buffer layer;
[0066] 10. An 80 nm thick silver film is deposited on the buffer layer obtained in step 9 to obtain an inorganic perovskite solar cell.
[0067] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 3 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.243 V and a short-circuit current density of 20.22 mA / cm². 2 The fill factor is 82.46%, and the efficiency is 20.72%.
[0068] Example 3:
[0069] This invention provides a method for fabricating inorganic perovskite solar cells based on stress-regulated phenylethyl phosphoric acid, comprising the following steps:
[0070] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned with detergent, deionized water and isopropanol for 30 min in sequence, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean ITO conductive glass substrate with good wettability.
[0071] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0072] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0073] 4. Dissolve CsI, HPbI3, and PbBr2 in a mixed solution of dimethylformamide and dimethyl sulfoxide in a 1:1 volume ratio (molar ratio), and add 1.5 mg / mL phenylethyl phosphoric acid. Heat and stir at 60°C under nitrogen atmosphere until completely dissolved to obtain a 1.0 mol / L CsPbI solution containing 1.5 mg / mL phenylethyl phosphoric acid. X Br 3-X Perovskite precursor solution;
[0074] 5. Spin-coat the perovskite solution obtained in step 4 onto the hole transport layer obtained in step 3 at a rotation speed of 2500 rpm / min for 90 s; then anneal at 180℃ for 5 min in ambient air; thus preparing an inorganic perovskite light-absorbing layer with a concentration of 1.0 mol / L containing 1.5 mg / mL phenylethyl phosphoric acid.
[0075] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain an electron transport layer solution;
[0076] 7. The electron transport layer solution obtained in step 6 was spin-coated onto the inorganic perovskite light-absorbing layer obtained in step 5 using a one-step spin-coating method. The spin-coating speed was 2000 rpm / min and the spin-coating time was 30 s to prepare the electron transport layer.
[0077] 8. Dissolve 0.5 mg BCP in 1 mL of isopropanol and stir until completely dissolved to obtain a buffer solution;
[0078] 9. Spin-coat the buffer layer solution obtained in step 8 onto the electron transport layer obtained in step 7 at a rotation speed of 5000 rpm / min and a spin-coating time of 30 s to prepare the buffer layer;
[0079] 10. An 80 nm thick silver film is deposited on the buffer layer obtained in step 9 to obtain an inorganic perovskite solar cell.
[0080] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 4 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.275 V and a short-circuit current density of 20.18 mA / cm². 2 The fill factor is 83.42%, and the efficiency is 21.46%.
[0081] Example 4:
[0082] This invention provides a method for fabricating inorganic perovskite solar cells based on stress-regulated phenylethyl phosphoric acid, comprising the following steps:
[0083] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned with detergent, deionized water and isopropanol for 30 min in sequence, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean ITO conductive glass substrate with good wettability.
[0084] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0085] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0086] 4. Dissolve CsI, HPbI3, and PbBr2 in a mixed solution of dimethylformamide and dimethyl sulfoxide in a 1:1 volume ratio (molar ratio), and add 3.0 mg / mL phenylethyl phosphoric acid. Heat and stir at 60°C under nitrogen atmosphere until completely dissolved to obtain a 1.0 mol / L CsPbI solution containing 3.0 mg / mL phenylethyl phosphoric acid. X Br 3-X Perovskite precursor solution;
[0087] 5. Spin-coat the perovskite solution obtained in step 4 onto the hole transport layer obtained in step 3 at a rotation speed of 2500 rpm / min for 90 s; then anneal at 180℃ for 5 min in ambient air; thus preparing an inorganic perovskite light-absorbing layer with a concentration of 1.0 mol / L containing 3.0 mg / mL phenylethyl phosphoric acid.
[0088] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain an electron transport layer solution;
[0089] 7. The electron transport layer solution obtained in step 6 was spin-coated onto the inorganic perovskite light-absorbing layer obtained in step 5 using a one-step spin-coating method. The spin-coating speed was 2000 rpm / min and the spin-coating time was 30 s to prepare the electron transport layer.
[0090] 8. Dissolve 0.5 mg BCP in 1 mL of isopropanol and stir until completely dissolved to obtain a buffer solution;
[0091] 9. Spin-coat the buffer layer solution obtained in step 8 onto the electron transport layer obtained in step 7 at a rotation speed of 5000 rpm / min and a spin-coating time of 30 s to prepare the buffer layer;
[0092] 10. An 80 nm thick silver film is deposited on the buffer layer obtained in step 9 to obtain an inorganic perovskite solar cell.
[0093] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 5 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.252 V and a short-circuit current density of 20.12 mA / cm². 2 The fill factor is 81.19% and the efficiency is 20.46%.
[0094] Example 5:
[0095] This invention provides a method for fabricating inorganic perovskite solar cells based on stress-regulated phenylethyl phosphoric acid, comprising the following steps:
[0096] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned with detergent, deionized water and isopropanol for 30 min in sequence, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean ITO conductive glass substrate with good wettability.
[0097] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0098] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0099] 4. Dissolve CsI, HPbI3, and PbBr2 in a mixed solution of dimethylformamide and dimethyl sulfoxide in a 1:1 volume ratio (molar ratio), and add 1.5 mg / mL phenylethyl phosphoric acid. Heat and stir at 60°C under nitrogen atmosphere until completely dissolved to obtain a 0.8 mol / L CsPbI solution containing 1.5 mg / mL phenylethyl phosphoric acid. X Br 3-X Perovskite precursor solution;
[0100] 5. Spin-coat the perovskite solution obtained in step 4 onto the hole transport layer obtained in step 3 at a rotation speed of 2500 rpm / min for 90 s; then anneal at 180℃ for 5 min in ambient air; thus preparing an inorganic perovskite light-absorbing layer with a concentration of 0.6 mol / L containing 1.5 mg / mL phenylethyl phosphoric acid.
[0101] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain an electron transport layer solution;
[0102] 7. The electron transport layer solution obtained in step 6 was spin-coated onto the inorganic perovskite light-absorbing layer obtained in step 5 using a one-step spin-coating method. The spin-coating speed was 2000 rpm / min and the spin-coating time was 30 s to prepare the electron transport layer.
[0103] 8. Dissolve 0.5 mg BCP in 1 mL of isopropanol and stir until completely dissolved to obtain a buffer solution;
[0104] 9. Spin-coat the buffer layer solution obtained in step 8 onto the electron transport layer obtained in step 7 at a rotation speed of 5000 rpm / min and a spin-coating time of 30 s to prepare the buffer layer;
[0105] 10. An 80 nm thick silver film is deposited on the buffer layer obtained in step 9 to obtain an inorganic perovskite solar cell.
[0106] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 6 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.275 V and a short-circuit current density of 19.68 mA / cm². 2 The fill factor is 83.65%, and the efficiency is 21.00%.
[0107] Comparative Example:
[0108] In contrast, this embodiment provides a method for preparing inorganic perovskite solar cells without the introduction of phenylethyl phosphoric acid, comprising the following steps:
[0109] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned with detergent, deionized water and isopropanol for 30 min in sequence, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean ITO conductive glass substrate with good wettability.
[0110] 2. Add 20 mg NiO XNiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0111] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0112] 4. Dissolve CsI, HPbI3, and PbBr2 in a mixed solution of dimethylformamide and dimethyl sulfoxide in a 1:1 volume ratio (molar ratio). Heat and stir at 60°C under nitrogen atmosphere until completely dissolved to obtain a 1.0 mol / L CsPbI solution. X Br 3-X Perovskite precursor solution;
[0113] 5. Spin-coat the perovskite solution obtained in step 4 onto the hole transport layer obtained in step 3 at a rotation speed of 2500 rpm / min for 90 s; then anneal at 180℃ for 5 min in ambient air; thus preparing an inorganic perovskite light-absorbing layer with a concentration of 1.0 mol / L.
[0114] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain an electron transport layer solution;
[0115] 7. The electron transport layer solution obtained in step 6 was spin-coated onto the inorganic perovskite light-absorbing layer obtained in step 5 using a one-step spin-coating method. The spin-coating speed was 2000 rpm / min and the spin-coating time was 30 s to prepare the electron transport layer.
[0116] 8. Dissolve 0.5 mg BCP in 1 mL of isopropanol and stir until completely dissolved to obtain a buffer solution;
[0117] 9. Spin-coat the buffer layer solution obtained in step 8 onto the electron transport layer obtained in step 7 at a rotation speed of 5000 rpm / min and a spin-coating time of 30 s to prepare the buffer layer;
[0118] 10. An 80 nm thick silver film is deposited on the buffer layer obtained in step 9 to obtain an inorganic perovskite solar cell.
[0119] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 7 As shown, at AM1.5, 100 mW / cm 2Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.207 V and a short-circuit current density of 20.18 mA / cm². 2 The fill factor is 81.14%, and the efficiency is 19.78%.
[0120] Example 6:
[0121] Unlike Examples 1-5, the conductive substrate in this example is any one of FTO conductive glass, transparent conductive flexible plastic, crystalline silicon substrate, and copper indium gallium selenide substrate.
[0122] Example 7:
[0123] Unlike Examples 1-6, the hole transport layer in this example is any one of 2PACZ, SAMs, PTAA, P3HT, P3CT, X55, and X60.
[0124] Example 8:
[0125] Unlike Examples 1-7, the electron transport layer in this example is C. 60 .
[0126] Example 9:
[0127] Unlike Examples 1-8, the buffer layer in this example is either ZnO or TPBi.
[0128] Example 10:
[0129] Unlike Examples 1-9, the metal electrode material in this example is either Au or Cu.
[0130] Example 11:
[0131] Unlike Examples 1-10, the solvent for the perovskite precursor solution in this example is any one or a mixture of two of γ-butyrolactone and N-methylpyrrolidone, or a mixture of them with any one or two of dimethylformamide and dimethyl sulfoxide.
[0132] Example 12:
[0133] Unlike Examples 1-11, the spin coating speed in this example is 1000 rpm / min and the time is 150 s.
[0134] Example 13:
[0135] Unlike Examples 1-12, the annealing conditions in this example are 100°C in air for 30 minutes.
[0136] Example 14:
[0137] Unlike Examples 1-13, the annealing conditions in this example are 210°C in air for 10 minutes.
[0138] In summary, this invention provides a method for preparing inorganic perovskite solar cells based on stress regulation using phenylethyl phosphoric acid. Phenylethyl phosphoric acid is introduced into the perovskite precursor solution to regulate the film stress and prepare inorganic perovskite solar cells. Through comparison of Examples 1-5 and the comparative examples, the phosphate groups in the phenylethyl phosphoric acid molecule exhibit strong coordination ability, capable of forming stable coordination bonds with undercoordinated lead ions present at perovskite grain boundaries or surfaces. This effectively passivates lead defects, significantly reduces the defect state density inside the film, and alleviates localized stress concentration caused by defects. Furthermore, the flexible alkyl segments in phenylethyl phosphoric acid can alleviate residual stress and suppress stress-induced lattice distortion and ion migration through fine-tuning of the molecular conformation, thereby improving the photoelectric performance and stability of the inorganic perovskite solar cells. Under the same conditions, the open-circuit voltage of the solar cells prepared in Examples 1-5 is 1.215 V-1.275 V, and the short-circuit current density is 19.68 mA / cm². 2 -20.28 mA / cm 2 The fill factor ranged from 81.19% to 83.65%, and the efficiency from 20.46% to 21.46%. In contrast, the comparatively prepared solar cell exhibited an open-circuit voltage of 1.207 V and a short-circuit current density of 20.18 mA / cm². 2 The fill factor is 81.14%, and the efficiency is 19.78%. The invention is effective.
[0139] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. An inorganic perovskite light-absorbing layer, characterized in that, The inorganic perovskite light-absorbing layer is obtained by dissolving ligand molecules in a perovskite precursor solution, depositing the layer using a one-step spin-coating method in a nitrogen atmosphere, and annealing it in an air atmosphere; the ligand molecules are phenylethyl phosphoric acid, and the concentration in the inorganic perovskite precursor solution is 0.5 ~ 3.0 mg / mL.
2. An inorganic perovskite solar cell based on stress-regulated phenylethyl phosphoric acid, characterized in that, The inorganic perovskite solar cell has the following structure stacked from bottom to top: a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a buffer layer, and a metal electrode; the perovskite light-absorbing layer is the inorganic perovskite light-absorbing layer described in claim 1, and its thickness is 300 ~ 900 nm.
3. The method for preparing an inorganic perovskite solar cell based on phenylethyl phosphoric acid for stress regulation as described in claim 2, characterized in that, Includes the following steps: (1) A hole transport layer is prepared on a conductive substrate; (2) An inorganic perovskite precursor solution containing the ligand molecule phenylethyl phosphoric acid was spin-coated onto the hole transport layer and then air-annealed to prepare a perovskite light-absorbing layer. (3) An electron transport layer is prepared on the perovskite light-absorbing layer; (4) Prepare a buffer layer on the electron transport layer; (5) Fabricate a metal electrode on the buffer layer; The concentration of the ligand molecule phenethyl phosphoric acid in the inorganic perovskite precursor solution is 0.5 ~ 3.0 mg / mL.
4. The preparation method according to claim 3, characterized in that, The spin coating speed is 1000 ~ 5000 rpm / min, and the time is 30 ~ 150 s.
5. The preparation method according to claim 3, characterized in that, The annealing conditions are: annealing at 100~210℃ in air for 5~30 min.
6. The preparation method according to claim 3, characterized in that, The solvent of the perovskite precursor solution is any one or a mixture of dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methylpyrrolidone, and the solute is CsPbI. X Br 3-X The concentration of the solute is 0.6 ~ 1.2 mol / L.
7. The preparation method according to claim 3, characterized in that, The conductive substrate is any one of FTO conductive glass, ITO conductive glass, transparent conductive flexible plastic, crystalline silicon substrate, and copper indium gallium selenide substrate; the hole transport layer is SAMs or NiO. X PTAA, P3HT, P3CT, X55, X60, or any one or more of these materials; the electron transport layer is PC. 61 BM, C 60 The material can be any one or two of the following: the buffer layer can be any one of BCP, ZnO, or TPBi; the material of the metal electrode can be any one of Au, Ag, Cu, or Al.
8. The application of a coordination molecule in inorganic perovskite solar cells, characterized in that, The coordination molecule is phenylethyl phosphoric acid. This ligand molecule is dissolved in a perovskite precursor solution, deposited using a one-step spin-coating method in a nitrogen atmosphere, and annealed in air to obtain an inorganic perovskite light-absorbing layer. Based on this coordination molecule, residual stress is released and defects are passivated, resulting in a high-quality perovskite thin film for the following structural devices: a. Inorganic or organic-inorganic hybrid perovskite single-junction solar cells; b. Inorganic or organic-inorganic hybrid perovskite / crystalline silicon tandem solar cells; c. Inorganic or organic-inorganic hybrid perovskite / organic tandem solar cells; d. Inorganic or organic-inorganic hybrid perovskite / copper indium gallium selenide tandem solar cells; e. All-perovskite tandem solar cells; f. All-inorganic perovskite tandem solar cells.
